Selection of Phalaenopsis amabilis (L.) Blume Orchid Resistance to Hygromycin - Mercuriani, Ixora (2012)
Examination of Phalaenopsis amabilis orchid resistance to hygromycin antibiotic is an important step to do prior to Agrobacterium-mediated genetic transformation in this orchids using Hygromycin phosphotransferase (HPT) gene as a selection marker in the T-DNA that harboring a desired gene to be transfered. We exposed the plant on hygromycin containing medium. The experiment was conducted using 6 weeks old P. amabilis protocorms. These protocorms were subcultured onto NP medium supplemented with various concentration of Hygromycin (0, 5, 10, 20, 1nd 40 mg.L-1). The number of survival protocorms were examined every week for 4 weeks after subcultured (WAS). The resistancy of hygromycin was calculated as ratio of death protocorms per total protocorms). The result showed that 10 mg.L-1 hygromycin with 1 weeks of application caused death close to LD 50. This data indicate that P. amabilis resistance to hygromycin treatment on the appropriate concentration 10 mg.L-1, and this concentration can be used for other purposes in orchid system